Trace metal concentrations in distilled alcoholic beverages and liquors in Nigeria. Issue 4 (29th September 2014) - Iwegbue, Chukwujindu M. A.; Overah, Loretta C.; Bassey, Francisca I.; Martincigh, Bice S.
<x xml:space="preserve">Abstract</x> The concentrations of 12 metals (Cd, Pb, Ni, Cr, Cu, Co, Fe, Mn, Zn, Ca, Mg and K) in 13 classes of alcoholic beverages were determined by atomic spectrometry after HNO3/H2O2 digestion. The mean concentrations of metals (µg mL−1) in these alcoholic beverages varied in the ranges 0.01–0.04, 0.02–0.24, 0.04–0.13, 0.01–0.28, 0.01–0.77, <0.001–0.12, 0.28–1.48, 0.004–0.33, 0.10–1.02, 1.43–162.86, 0.26–25.46 and 0.49–322.58 for Cd, Pb, Ni, Cr, Cu, Co, Fe, Mn, Zn, Ca, Mg and K respectively. The concentrations of metals found in these particular alcoholic beverages were below the International Statutory Limits for metals in alcoholic beverages. The estimated daily intake of the metals based on a per capita consumption of 3.6 L per annum pure alcohol was <3% of the tolerable daily intake of each metal. The individual and combined target hazard quotients of the metals were <1, indicating no long‐term health concerns from the consumption of these alcoholic beverages based on their metal content alone. Copyright © 2014 The Institute of Brewing & Distilling